Longitudinal patterns of fish assemblages in mountain streams from tropical forest biome - Marques da Silva, Joao Fernando; Raio, Cibele Bender [UNESP]; Silva Bernardino, Debora Fernandes; Bennemann, Sirlei Terezinha (Revista Biota Neotropica, 2013)
The aim of this study was to verify structure patterns in fish assemblages in mountain streams of the Rio Tibagi basin through the characterization of spatial and temporal variations in the composition of fish species. Samples were collected in three segments of the Varanal, Joao Pinheiro and Rio Preto streams. We collected 1154 specimens belonging to 21 species. The most abundant orders were Characiformes (59.01 +/- 2.84%) and Siluriformes (39.34 +/- 2.82%). Phalloceros harpagos was the most abundant species with 433 individuals, followed by Trichomycterus aff. davisi, with 292 individuals. No temporal variations (between seasons) were detected, but the cluster analysis suggests a separation of species composition between the segments closer to the headwaters and those more distant. The first two axes of the Canonical Correspondence Analysis (CCA) explained 80.09% of the variation in species abundance, and the variables that structured the fish assemblages in those streams were the stream width, depth, water speed, flow rate, conductivity and pH.
Keywords: ichthyofauna; freshwater fishes; neotropical fishes; low order streams; Tibagi river basin